A gender-based analysis of performance of small and medium printing firms in Metro Manila - Malaya, Milagros F. (Animo Repository, 2004)
Increasing the participation of women in entrepreneurship is critical to a country's long term economic growth. This conclusion was drawn from the ground-breaking research conducted worldwide by the Global Entrepreneurship Monitor (GEM, 2000). In order to provide support for women currently in business and encourage more women to start their own businesses, the need arises to expand the knowledge base about female entrepreneurs. This study, therefore, attempts to answer some of the questions raised about women and their businesses. The objectives of the research are to present a comparative analysis of the performance of men-owned and women-owned businesses using a multidimensional framework of entrepreneurial success, and to investigate the extent of influence of selected factors (management style and strategies) on their success. The success indicators refer to the financial, nonfinancial and personal goals indicated in literature as being important to entrepreneurs. Data for the study were obtained from the member companies of the Printing Industries Association of the Philippines, Inc. (PIAP). The descriptive, relational and causal designs were employed with the following statistical tools: percentage distributions, summary statistics (mean, median, standard deviation), t-test for mean differences, multiple linear regression modeling and the ANOVA (analysis of variance) interaction graphs. The major findings indicate that in the printing services sector: 1) There were no significant disparities between men and women owners in terms of their individual characteristics and firm attributes, following global trends. 2) On the primary variable of firm financial performance (measured as sales, net performance, and change in assets), while no empirical support was found for gender influence on the short-term scale (2003), there appeared to be basis for gender difference over the longer time period of three years, providing support for the female underperformance hypothesis (Du Rietz and Henrekson, 2000). 3) The results of the ratings on success indicators concurred with literature review that both sexes valued financial and nonfinancial success, but attending to personal goals was more important to women. 4) Comparing the genders, usage of each management style was practically the same except that the directive style was employed by more women, and the participative style was employed by more men. 5) Variations attributed to gender were found in terms of the strategies used in the daily operations of the company, specifically on practices dealing with job policies and procedures, employee benefits, labor relations, pricing policies, product / service issues, credit, financial control and growth aspirations. 6) Data analysis did not provide support for the contention that firm financial performance could be related to people-oriented management styles (referring to participative, developing, delegating). Higher performance was observed in using the negotiating management style poorer performance was indicated for the developing style. 7) Factors asserted to significantly affect financial firm performance were: age and birth order of the entrepreneur, work and business background, size and age of the firm, risk-taking propensity, management style, training of supervisors / employees, performance evaluation of supervisors, pricing policies, promotional tools, bank loans and investment plans for growth. 8) Interaction effects were detected, signifying that gender moderated the relationship between firm financial performance and each of the management factors (risk-taking propensity, training of workers, performance evaluation, product / service issues, primary promotional tools, financial control and investment plans for growth). This indicated that while there were no direct effects of gender on short-term financial performance, gender nevertheless exercised an indirect effect through its effects on the management factors with significant impact on performance. The findings of the study strongly suggest that certain differences between men and women business owners may be more fundamental in nature and a feminist perspective is warranted to appropriately evaluate the performance of women-owned businesses. The final part gave suggestions on directions for future research on women entrepreneurs and recommendations to the industry.